The relationship between training load, physical performance and physiological adaptations in Rugby football players: A systematic review - Eduardo Paiva; Sérgio Valentim; Tiago Reis; José E. Teixeira; Luis Branquinho; Álvaro Fortunato; Pedro Forte (Desafio Singular, 2024)
Applying appropriate training loads in accordance with the defined objectives promotes optimal physical and physiological adaptations, reduces the likelihood of illness and injury and therefore increases the possibility of success during the Rugby. The aim of this review was to compile and systematize the information in the literature on the association between training load variables (internal and external) and performance outcomes in Rugby. As such, the main objective will be to conduct a systematic review of the published literature to identify the physical and physiological performance variables in Rugby sport to monitor the training load. Following the preferred reporting item for systematic reviews and meta-analyses (PRISMA) and PICOS approach, the search was conducted systematically only in the PubMed database, which, in itself, also restricts the search spectrum of the paper, thus conferring a limitation to the present academic work. The search included specific terms - namely, Rugby; Training Load; - throughout the possible temporal spectrum in PubMed, since there is still little robustness in the literature of the content in question in the sport of Rugby. Articles were selected using pre-defined selection criteria, namely observational studies, randomized clinical studies, and clinical trial studies. The initial electronic search with the variables "Training Load", "Rugby" led to a set of 114 articles, of which only 96 articles were selected after the selection of variables for presenting observational study designs and/or randomized clinical trials. A further screening was carried out, and based on the inclusion criteria of the papers, the result of the analysis of the relevance of the studies was only 19 articles. Three duplicates were eliminated, therefore, the final set of analysis resulted in 16 articles. From the studies compiled in this review, it seems that there is a strong correlation between the perceived exertion (RPE) and the prescription and definition of the training load applied in Rugby athletes. The RPE reflects the most applied and analyzed variable throughout all the studies. Several articles reflect that there is a strong relationship between the training load, and the inter-individual capacity of each athlete and their tolerance to the load (player load).